Editorial - Andreou, Andreas S.; Papadopoulos, Harris; Iliadis, Lazaros S. (My University, 2012)
This special issue of the International Journal on Artificial Intelligence Tools (IJAIT) hosts a selection of extended versions of papers presented in the 6th IFIP International Conference on Artificial Intelligence Applications and Innovations (AIAI 2010). After a peer review process, a total of 48 papers authored by scientists from 16 countries were accepted and presented at the conference, which was held in Larnaca, Cyprus on the 6th and 7th of October, 2010. IFIP’s AIAI is an annual meeting that grows in significance every year, attracting researchers from different countries around the globe. It maintains high quality standards and welcomes research papers describing prototypes, innovative systems, tools and techniques of AI, as well as applications of AI in real-world problems.